2009
DOI: 10.1128/aac.01088-08
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin Ototoxicity: a Reevaluation in an Era of Increasing Doses

Abstract: Nephrotoxicity and ototoxicity have historically been documented as relatively rare complications of vancomycin monotherapy. Recent reports have linked aggressive vancomycin dosing strategies to significant risks of nephrotoxicity. We evaluated the rate of high-frequency hearing loss detected by audiometry for patients on vancomycin therapy. For this purpose, we used retrospective case-control analysis of audiometry results for patients on vancomycin therapy for whom baseline and follow-up exams were available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 19 publications
4
47
2
1
Order By: Relevance
“…However, HD-vancomycin regimens have been associated with an increased risk of nephrotoxicity compared to that from standard dosing, particularly when vancomycin is combined with another nephrotoxic agent (15). Concerns regarding a significant risk for vancomycin-induced ototoxicity among older patients treated with HD-vancomycin have also been raised (11). Furthermore, recent expert panel recommendations regarding vancomycin therapeutic drug monitoring have proposed a target AUC/MIC ratio of Ͼ400 (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, HD-vancomycin regimens have been associated with an increased risk of nephrotoxicity compared to that from standard dosing, particularly when vancomycin is combined with another nephrotoxic agent (15). Concerns regarding a significant risk for vancomycin-induced ototoxicity among older patients treated with HD-vancomycin have also been raised (11). Furthermore, recent expert panel recommendations regarding vancomycin therapeutic drug monitoring have proposed a target AUC/MIC ratio of Ͼ400 (25).…”
Section: Discussionmentioning
confidence: 99%
“…Some practitioners have extrapolated these dosing recommendations with associated trough concentration goals to all vancomycin use. However, evidence of superior efficacy is lacking, and results of several single-center, mostly retrospective trials have suggested that this more aggressive dosing may be related to an increased incidence of vancomycin-related nephrotoxicity (12,14,18,20,27) and ototoxicity (9). The results and conclusions of these studies have been questioned, to varying degrees, due to design limitations, including the failure to account for other risk factors for renal compromise, and/or their single-center nature.…”
mentioning
confidence: 99%
“…This child was treated with amikacin and vancomycin at mean doses of 180 mg/m 2 /day and 120 mg/m 2 /day, respectively. The ototoxic effect of vancomycin has already been proven (11,12) . It is especially notable when vancomycin is used in association with other potentially ototoxic drugs (13) , which was not the case with this child.…”
Section: Discussionmentioning
confidence: 99%